Tales from the Clans: Warriors Novellas # 4-6 - Hunter, Erin (New York, NY : Harper, an imprint of HarperCollins Publishers, 2014)
"How did Tigerclaw go from exiled warrior to ShadowClan leader? Which StarClan cats helped shield Leafpool's secret from ThunderClan? What happened to Dovewing's powers after the great battle with the Dark Forest? Discover more untold stories from the warrior Clans in these three gripping tales--together in print for the first time!"--Back cover.
Tigerclaw's fury -- Leafpool's wish -- Dovewing's silence.
new kids book 2023 winter.
Keywords: Cats -- Juvenile fiction; Adventure fiction; Fantasy fiction